MORPHOLOGICAL CHARACTERS OF CHILLI PEPPER (Capsicum frutescens L.) AS INFLUENCED BY SODIUM AZIDE AT GENERATIVE STAGE OF M1 GENERATION - Saraswati, I Gusti Agung Eka; Pharmawati, Made; Junitha, I Ketut (Jurnal Biologi Udayana, 2013)
Chili pepper ( Capsicum frutescens L.) is one vegetable crop that has high economic value.  There are several problems in cultivation of chili pepper, for examples limited land, bad weather, and pests and diseases, which result in low production. These problems can be solved by developing new cultivar which has superior quality.  New cultivars of chili pepper plants can be obtained through induced mutation using chemical mutagen. In this research sodium azide (NaN 3 ) was used as mutagen in chili pepper in order to obtain genetic variations that are useful in  increasing its  production.  The research was designed in  randomized  block  design. The observations were made on the response of plant morphology at generative stage, including plant height, number of branch, number of leaf, leaf length and leaf width.  The results showed that sodium azide increased plant height, branch number, leaf number and leaf length.  Sodium azide at concentrations of 2 mM and 5 mM were most effective in increasing plant height, number of leaves and number of branches. Keywords: Capsicum frutescens L., morphology, mutation, sodium azide